2014
DOI: 10.1016/j.fsigen.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gender on eye colour variation in European populations and an evaluation of the IrisPlex prediction model

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. In this study, we investigate the role of gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
48
2
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 21 publications
6
48
2
5
Order By: Relevance
“…In a subsequent study, Pietroni et al [37] found gender to be significantly associated with quantitative eye color measurements in an Italian population sample, but not in a Danish and a Swedish sample. Notably, a gender effect on quantitative eye color was observed before by Liu et al [33], but in this study it only explained 0.04% of hue and 0.09% of saturation in the Dutch population studied, while in the Italian population analysed by Pietrone et al [37], gender explained 4.9% of the PIR-score that is based on saturation. Pietrone et al [37] concluded that the gender effect on eye color may be a population specific phenomenon.…”
Section: Eye Colormentioning
confidence: 90%
See 4 more Smart Citations
“…In a subsequent study, Pietroni et al [37] found gender to be significantly associated with quantitative eye color measurements in an Italian population sample, but not in a Danish and a Swedish sample. Notably, a gender effect on quantitative eye color was observed before by Liu et al [33], but in this study it only explained 0.04% of hue and 0.09% of saturation in the Dutch population studied, while in the Italian population analysed by Pietrone et al [37], gender explained 4.9% of the PIR-score that is based on saturation. Pietrone et al [37] concluded that the gender effect on eye color may be a population specific phenomenon.…”
Section: Eye Colormentioning
confidence: 90%
“…The authors reemphasized that in their samples females tended to present darker eye colors than predicted by IrisPlex in a significantly higher proportion than males [41]. In a subsequent study, Pietroni et al [37] found gender to be significantly associated with quantitative eye color measurements in an Italian population sample, but not in a Danish and a Swedish sample. Notably, a gender effect on quantitative eye color was observed before by Liu et al [33], but in this study it only explained 0.04% of hue and 0.09% of saturation in the Dutch population studied, while in the Italian population analysed by Pietrone et al [37], gender explained 4.9% of the PIR-score that is based on saturation.…”
Section: Eye Colormentioning
confidence: 94%
See 3 more Smart Citations